1989
DOI: 10.1104/pp.90.2.617
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Properties and Composition of Reaction Center and Ancillary Polypeptide Complexes of Photosystem II Deficient Mutants of Synechocystis 6803

Abstract: The polypeptide composition and spectral properties of three photosystem 11 (PSII) deficient mutants of the cyanobacterium Synechocystis 6803 have been determined. The levels of the 43 and 47 kilodalton chlorophyll-binding proteins and the reaction center component D2 are affected differently in each mutant; the 33 kD polypeptide of the oxygen-evolving complex is found at wild-type levels in all three. The 43 and 47 kilodalton proteins are implicated as important elements in the assembly and/or stability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

1991
1991
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…Therefore we assume that the observed fluorescence and its structure is predominantly due to the antenna complex. In agreement with Dzelzkalns and Bogorad (1989) we assign the 686 nm band in active particles to CP 43 and the 690 nm shoulder to CP 47 (Fig. I).…”
Section: Low Temperature Fluorescencesupporting
confidence: 86%
“…Therefore we assume that the observed fluorescence and its structure is predominantly due to the antenna complex. In agreement with Dzelzkalns and Bogorad (1989) we assign the 686 nm band in active particles to CP 43 and the 690 nm shoulder to CP 47 (Fig. I).…”
Section: Low Temperature Fluorescencesupporting
confidence: 86%
“…The peak at 650 nm is emitted from phycocyanin in the PBS. The peak at 685 nm is a combination of emissions from the terminal energy acceptors of the PBS (around 680 nm; Gantt and Lipschultz 1973;Gantt et al 1979) and from CP43, one of the Chl-binding proteins associated with PS II (around 686 nm; Pakrasi et al 1985;Dzelzkalns and Bogorad 1989;Nilsson et al 1992;Haag et al 1993 . 1992).…”
Section: Changes In Fluorescencementioning
confidence: 99%
“…1992). The peak at 695 nm probably reflects emissions from both CP47 (another Chl-binding protein associated with PS 11) and the reaction center of PS I1 (Pakrasi et al 1985;Dzelzkalns and Bogorad 1989;Nilsson et al 1992;Haag et al 1993). Finally, the shoulder at 7 15 nm is a consequence of fluorescence emission from PS I Chl.…”
Section: Changes In Fluorescencementioning
confidence: 99%
“…that affect the accumulation of CP43 (Rochaix et al, 1989;Dzelzkalns & Bogorad 1989;Carpenter et al, 1990). These have all shown that the inability to accumulate CP43 results in reduced levels of CP47, Dl, and D2.…”
mentioning
confidence: 99%